1990
DOI: 10.1017/s0033291700017700
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal eating attitudes in London schoolgirls — a prospective epidemiological study: outcome at twelve month follow-up

Abstract: SynopsisThe occurrence and course of eating disorder in a large representative population of 15-year-old London schoolgirls has been assessed using a two-stage survey methodology. Attempts to control weight were common and often transient. Dieting was in the great majority of girls found to be a benign practice without progression to more extreme concerns about food and weight. However, a small proportion of dieters did become cases and formed the majority of new cases found at follow-up. The relative risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
284
2
10

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(313 citation statements)
references
References 24 publications
17
284
2
10
Order By: Relevance
“…This is concerning, given that dieters of normal body weight have been found to be eight times more likely to develop an eating disorder than their non-dieting counterparts. 36 It has been noted that women who have developed cognitive schemas that associate being underweight with positive attributes report higher eating disorder symptoms. 37 In this study, being underweight rather than the correct weight appeared to be viewed by many subjects as desirable.…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning, given that dieters of normal body weight have been found to be eight times more likely to develop an eating disorder than their non-dieting counterparts. 36 It has been noted that women who have developed cognitive schemas that associate being underweight with positive attributes report higher eating disorder symptoms. 37 In this study, being underweight rather than the correct weight appeared to be viewed by many subjects as desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Both retrospective and prospective studies in adolescents have found self-reported dieting to predict bulimic symptoms (Field, Camargo, Taylor, Berkey, & Colditz, 1999;Stice & Agras, 1998) and eating-related psychopathology (Leon, Fulkerson, Perry, Keel, & Klump, 1999;Patton, Johnson-Sabine, Wood, Mann, & Wakeling, 1990;Santonastaso, Friederici, & Favaro, 1999). Such results have been interpreted as consistent with restraint theory, which posits that dietary restriction should increase the risk for the onset of binge eating and bulimic pathology (Polivy & Herman, 1985).…”
Section: Introductionmentioning
confidence: 93%
“…5 This has caused concern, because food restriction is seen not only as a threat to the nutritional status of children, but also as a risk factor in the development of eating disorders. 6 Patton 7 pointed out that the relative risk of developing eating disorders is eight times higher in dieting as compared to non-dieting 15-y-old girls. In a subsequent study of Patton,8 female subjects that dieted excessively were 18 times more likely to develop an eating disorder within 3 y than those that did not diet.…”
Section: Introductionmentioning
confidence: 99%